2011
DOI: 10.1007/s00436-011-2576-0
|View full text |Cite
|
Sign up to set email alerts
|

Small ruminant resistance against gastrointestinal nematodes: a case of Haemonchus contortus

Abstract: Gastrointestinal nematode (GIN) infections are a common constraint to small ruminant industry throughout the world, and among those, haemonchosis has its own significance. Control of GIN primarily relies on the use of anthelmintics, but this approach has become less reliable due to the development of resistance in GINs against commonly used anthelmintics and an increased consumer demand for environmentally friendly animal products. These issues have stimulated investigations to find alternative sustainable con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 182 publications
(164 reference statements)
0
36
0
1
Order By: Relevance
“…The host immune system can regulate nematode female length. There is a significant association between increased IgA activity against larvae and reduced Hc female length (Strain & Stear, 2001;Saddiqi et al, 2011). Moreover, host breed (Aumont et al, 2003), host gender (Gruner et al, 2004), diet (Hoste et al, 2008) and concurrent parasitic infection (Reinecke et al, 1982;Terefe et al, 2005) can affect nematode length.…”
Section: Discussionmentioning
confidence: 99%
“…The host immune system can regulate nematode female length. There is a significant association between increased IgA activity against larvae and reduced Hc female length (Strain & Stear, 2001;Saddiqi et al, 2011). Moreover, host breed (Aumont et al, 2003), host gender (Gruner et al, 2004), diet (Hoste et al, 2008) and concurrent parasitic infection (Reinecke et al, 1982;Terefe et al, 2005) can affect nematode length.…”
Section: Discussionmentioning
confidence: 99%
“…The PPR is considered a risk factor for pasture contamination and kids are often exposed to this infection (Saddiqi et al, 2011). The PPR has been well recorded in sheep (Armour 1980;Gibbs 1986;Barger 1993) and goats (Rahman and Collins 1992;Dorny et al, 1995;Baker et al, 1998;Chartier et al, 1998;Mandonnet et al, 2005).…”
Section: Host Reproductive Statusmentioning
confidence: 99%
“…In sheep, it has been reported that younger animals are usually more infected by GINs than adults Saddiqi et al, 2011). Lambs have been reported to be better able to resist GIN challenge after puberty (Saddiqi et al, 2011) andSchallig (2000) reported that lambs under six months of age were more susceptible to infection than older sheep.…”
Section: Age Of Hostmentioning
confidence: 99%
See 2 more Smart Citations